The origins of the British welfare state : - Harris, Bernard (Palgrave Macmillan, 2004)
This book provides a comprehensive introduction to the history of social welfare and social policy in Britain before the modern welfare state. It examines the role played by voluntary social provision (including self-help and mutual aid), as well as the growth of state intervention, in meeting welfare needs. It offers detailed coverage of all the main areas of social policy and provides an introduction to the competing theoretical explanations for the growth of welfare states over the last 200 years.